2013
DOI: 10.1097/qad.0b013e32835f1d8c
|View full text |Cite
|
Sign up to set email alerts
|

Increasing HIV testing among male partners

Abstract: A simple prenatal intervention taking into account the couple relationship increases the uptake of HIV testing among men in different socio-cultural settings. COC could contribute to the efforts towards eliminating mother-to-child transmission of HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 21 publications
0
60
0
Order By: Relevance
“…The core components of VCT studies included individual and couples HIV (rapid) testing and counseling, education and role-play (skills-building and self-efficacy), condom distribution, and information and referral for treatment, where necessary [12, 17, 20, 21, 27, 29, 30, 5057]. …”
Section: Resultsmentioning
confidence: 99%
“…The core components of VCT studies included individual and couples HIV (rapid) testing and counseling, education and role-play (skills-building and self-efficacy), condom distribution, and information and referral for treatment, where necessary [12, 17, 20, 21, 27, 29, 30, 5057]. …”
Section: Resultsmentioning
confidence: 99%
“…(19) found that couples’ HCT seemed to threaten masculine esteem by exposing their extra-marital relations and consequently severing their relations with their female spouses. Despite these fears, there is evidence that targeting men to encourage them to test for HIV together with their partners can improve uptake of couples’ HCT (40), and a recent randomized trial has suggested that targeting men as a specific population sub-group could improve couples’ HCT uptake especially at antenatal clinics (41). …”
Section: Discussionmentioning
confidence: 99%
“…Studies across sub-Saharan Africa report rates of male partner HTC ranging from 5%-33%, with the majority reporting that less than one in five men get HIV tested during their partner's pregnancy (Figure 2). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] A retrospective evaluation of PMTCT medical records in a referral hospital in Uganda showed that less than 5% of male partners underwent HTC. 21 Another randomized trial in Uganda that offered a written invitation or information note resulted in only 15% male partner testing.…”
Section: Low Rates Of Male Partner Involvement In Pmtct and Antenatalmentioning
confidence: 99%